SENGKETA STATUS SILALA ANTARA BOLIVIA DAN CHILE BERDASARKAN UNWC 1997: Dispute on the Status of Silala Between Bolivia and Chile Based on UNWC 1997 - Balqis, Devina Nuzlia; Budianto, Anto Ismu (AMICUS CURIAE, 2024)
Territorial disputes are border issues between countries that often occur internationally. As happened in the relationship between Bolivia and Chile regarding the dispute over the Silala River, the use of Silala waters began in 1906. Where the two countries were involved in disputes regarding the status and use of Silala. Bolivia emphasized that the Silala spring did not meet the requirements to be considered an international waterway due to the canalization and that Chile had to pay compensation. On the other hand, Chile claims Silala as an international waterway. With these overlapping claims, Silala disputes cannot avoided. This dispute was submitted to the International Court of Justice by Chile on June 6, 2016. This research examines the status of Silala based on UNWC 1997 and the efforts taken by the two countries in resolving the Silala waters dispute. This research is a normative legal research that was collected based on literature studies and analyzed qualitatively with deductive methods and using secondary data. From